Socio-Economic Determinants of the Financial Inclusion of Women and Men in Burkina Faso: An Analysis using the Sequential Logit Model - Compaore, Dimaviya Eugène; Maiga, Boukaré (International Journal of Economics and Financial Issues, 2024)
This article identifies and analyses the socio-economic determinants of financial inclusion. Using data from the FinScope survey (2016) in Burkina Faso, a sequential logit model was used on a sample of 5012 individuals. The results indicate that level of education, age, access to television, urban location, marital status and time to access a bank branch are the main determinants of the first phase of the financial inclusion process. In the second phase of the process, level of education, age, access to television, urban location, marital status and time spent accessing a bank branch emerged as determinants of access to savings. In the third and final phase of the process, household size, access time to a bank branch and confidence in financial institutions were the only determinants of access to credit. The results also show a difference between the factors influencing financial inclusion for men and women.